The influence of physical exercise on oestrogen and androgen receptor expression in a chemically and hormonally-induced rat model of prostate cancer - Nascimento-Gonçalves, E (2021)
Background: Oestrogen (ER) and androgen (AR) recep- tors play an important role in normal prostate development and are also implied in prostate cancer (PCa) development. Several studies suggested that physical activity may decrease the risk of PCa development and also changes sexual hor- mones and their receptors. This study aimed to evaluate the effects of physical exercise on ERα and AR expression in a rat model of chemically and hormonally-induced PCa. Materials and Methods: Fifty-five male Wistar Unilever rats of 12 weeks of age were randomly divided into four groups: control sedentary (n = 10), control exercised (n = 10), induced sedentary (n = 15) and induced exercised (n = 20). Animals from exercised groups started the exercise training in a treadmill (Treadmill Control LE 8710, Harvard Apparatus, USA), at the age of 8 weeks, for 35 weeks (5 days/week). The protocol for PCa induction started at 12 weeks of age and consisted of sequential administration of flutamide (50 mg/kg, TCI Chemicals), testosterone propion- ate (100 mg/kg, TCI Chemicals) and N-methyl-N-nitrosourea (30 mg/kg, Isopac®, Sigma Chemical Co.), followed by sub- cutaneous implants of crystalline testosterone. Animals were sacrificed at 61 weeks of age and a complete necropsy was performed. All experiments were approved by DGAV (no. 021326). Antibodies for Erα (1:500, clone 6F11, Novocastra) and AR (clone PG21, Merck Millipore) were used for the immunohistochemical study. The staining extension was evaluated in normal prostate tissue and in dorsolateral pros- tate lesions (hyperplasia, dysplasia, prostatic intraepithelial neoplasia (PIN) and microinvasive carcinoma) and assessed to five levels (0%, <25%, 25-50%, 50-75% and >75%), con- sidering the extension of immunopositive tissue. Data was analysed with SPSS 25.Results: The normal prostate tissue and dorsolateral prostate lesions of animals from all groups were immunopositive for Erα and AR. However, the groups showed high immunoposi- tivity for AR and low positivity for Erα (<25% in all groups) with similar values between both control and induced groups (p > 0.05). The malignant lesions (PIN and microinvasive carcinoma) showed lower AR expression when compared with normal prostate tissue in all groups. Conclusions: As expected, the AR expression was lower in malignant lesions. Inversely to that reported in other studies, the exercise training did not modify the ERα and AR expres- sion, which may be related to the duration and type of exer- cise performed.